Analisis Kualitas Air dan Kepadatan Moluska pada Kawasan Ekosistem Mangrove, Nusa Lembongan - Made Ayu Pratiwi; Ni Made Ernawati (Journal of Marine and Aquatic Sciences, 2016)
Mangrove is one of the coastal ecosystem is able to grow in fluctuating water conditions. Mangrove areas are found on the Nusa Lembongan island, Bali, is a ??mangrove ecosystem that have the unique characteristics of water area. The mangrove area is located on one of the small islands in Bali that have no source of freshwater input and there is the entrance of water into the mangrove forest. The uniqueness of waters in mangrove ecosystem will affect the type and density of fauna associated, particularly mollusca. Mollusca are one of the animals that live and thrive in the mangrove ecosystem. Therefore, it is necessary to study which aimed to provide a description of the water quality and mollusca on mangrove ecosystem in Nusa Lembongan. This research was conducted in June 2015 on a six station observation. Measurement of water quality conducted on four water parameters such as temperature, DO, pH, and salinity. Observation on the type and density of mollusca done using transects squared (1 x 1 meter). The range of values ??obtained water quality parameters, such as; 1) salinity (32.00-34.33 ppm), 2) pH (7.06-7.96), 3) temperature (27.27-30.13 Celsius), and 4) DO (2.60-6.90 mg/l). Water quality parameter values ??obtained are still in the range of water quality standard and suitable place to live and grow for marine biota life. Dissolved oxygen (DO) value was still below the threshold quality standard. There six families of mollusca found in six observation station, such as Neritidae, Littorinidae, Columbellidae, Olividae, Carditidae, Muricidae, Potamidae, Certthiidae. The highest density was in Family Potamidae (1.83 ind/m2), so the Family Potamidae is able to adapt and have a wide area deployment.